Nutritional and sensory enhancement of traditional wheat-based yeasted steamed dumplings through oat flour fortification - Havrlentová, Michaela; Jurkaninová, Lucie; Švec, Ivan; Jánoška, Daniel; Klimáčková, Jana; Hendrichová, Jana; Hozlár, Peter; Gavurníková, Soňa (Frontiers in Nutrition, 2025)
This study investigated the chemical composition and sensory acceptability of yeasted steamed wheat dumplings – a typical Central European side dish – that were fortified with wholegrain oat flours derived from two distinct cultivars – hull-less Inovec and hulled Prokop. The flours were used at 7 substitution levels, ranging from 2.5 to 25.0%. Chemical analysis of both flour mixtures and steamed dumplings revealed a significant modulation of macronutrient profiles with increasing oat inclusion. As presumed, the β-d-glucans content increased proportionally with the addition of oats, reaching up to 1.23% in flour mixtures (Prokop) and 0.80% in steamed dumplings (Inovec). Furthermore, enrichment by oat resulted in higher protein (up to 15.05%), lipid (up to 12.13%), and dry matter contents, while reducing starch levels. Two-factorial ANOVA attributed the most variance in nutritional traits (e.g., 87% for β-d-glucans) to the level of wheat flour substitution, with minor effects coming from the oat variety. The correlation analysis confirmed strong formulation-dependent trends, particularly for β-d-glucans (r = 0.972), lipids (r = 0.919), and proteins (r = 0.831), with the thermal stability of key nutrients demonstrated in all processing stages. Sensory evaluation revealed an inverse relationship between oat content and dumplings acceptability, primarily due to undesirable changes in color, aroma, and texture at higher inclusion levels. Multivariate PCA and two-way joining heatmap analysis highlighted that measurable nutritional enhancement was evident from the addition of just 2.5% oat flour, while the most favorable balance between an improved nutrient profile and retained sensory attributes was observed at inclusion levels of 10–15%. Oat Inovec-enriched samples exhibited superior protein and lipid content yet were more prone to sensory degradation at high inclusion rates. Overall, fortification with oat flours at levels of up to 10–15% is identified as an effective strategy for developing nutritionally enriched, fiber-rich yeasted steamed products with minimal sensory compromise. The findings emphasize the importance of balancing nutritional gains with sensory acceptability in the design of functional cereal-based foods.